Real‐time continuous glucose monitoring improves postoperative glucose control in people with type 2 diabetes mellitus undergoing coronary artery bypass grafting: A randomized clinical trial - Son, Heejun; Sohn, Suk Ho; Kim, Hyun Ah; Choe, Hun Jee; Lee, Hyunsuk; Jung, Hye Seung; Cho, Young Min; Park, Kyong Soo; Hwang, Ho Young; Kwak, Soo Heon (Diabetes, obesity & metabolism, 2025)
Background Effective glycaemic control following cardiac surgery improves clinical outcomes, and continuous glucose monitoring (CGM) might be a valuable tool in achieving this objective. We investigated the effect of real‐time CGM and telemonitoring on postoperative glycaemic control in people with type 2 diabetes (T2D) after coronary artery bypass grafting (CABG). Methods In this randomized clinical trial (RCT), adults with T2D undergoing CABG were assigned to either a test group utilizing real‐time CGM (Dexcom G6) and telemetry for glycaemic control, or a control group with blinded CGM measures, relying on point‐of‐care measures. The primary outcome was the percentage of time in range (TIR) of blood glucose between 70 and 180 mg/dL (3.9–10.0 mmol/L), measured by CGM. Results Among 91 subjects, 48 were in the test group and 43 were in the control group. The least squares (LS) mean ± standard error of TIR was 60.3 ± 2.7%, 50.3 ± 2.9% in the test and control group, respectively. The test group had significantly higher TIR when adjusted with age, sex, body mass index, baseline fasting blood glucose and baseline glycated haemoglobin (LS mean difference, 10.0%; 95% confidence interval, 2.1–18.0; p = 0.014). The test group also had lower time above range and mean glucose levels, with no differences in time below range or hypoglycaemic events. Conclusions In this RCT, real‐time CGM and telemonitoring improved glycaemic control during postoperative period without increasing hypoglycaemia risk. Given the benefits of effective glycaemic control on perioperative outcomes, CGM may be helpful in managing T2D after CABG.